Anticipated Raw Materials Price Shocks and Monetary Policy Response - A New Keynesian Approach - Roland C. Winkler; Hans-Werner Wohltmann (Kiel University, Department of Economics, 2006)
The paper analyzes the dynamic effects of anticipated raw materials price increases for small open oil-dependent economies and investigates the consequences of several monetary policy rules in response to commodity price shocks. Based on a calibrated New Keynesian open economy model the analysis shows that anticipated increases in the price of oil will involve oil-dependent economies both in temporary inflation and deflation as well as in output expansion and contraction. Compared to an interest rate Taylor rule a money growth rule is more appropriate to reduce the volatility of the CPI inflation rate whereas just the opposite holds for stabilizing the output gap.
Keywords: E32; E52; F41; Q43; 330; Oil price shocks; Monetary Policy; Open Economy; Mineralölpreisschock; Inflationserwartung; Geldpolitik; Kleines-offenes-Land; Ungleichgewichtstheorie; Dynamisches Modell; Taylor-Regel; Geldmengensteuerung; Wirtschaftspolitische Wirkungsanalyse; Theorie